Adaptation by Type III CRISPR-Cas Systems: Breakthrough Findings and Open Questions - Zhang, Xinfu; An, Xinmin (Frontiers in Microbiology, 2022)
CRISPR-Cas systems acquire heritable defense memory against invading nucleic acids through adaptation. Type III CRISPR-Cas systems have unique and intriguing features of defense, and are important in method development for Genetics research. We started to understand the common and unique properties of type III CRISPR-Cas adaptation in recent years. This review summarizes our knowledge regarding CRISPR-Cas adaptation with the emphasis on type III systems, and discusses open questions for type III adaptation studies.